Settlement Agreement in the Process of Resolving Administrative Disputes: Experience of Ukraine and Russia - A. D. Sydielnikov (Сибирское юридическое обозрение, 2015)
The article is devoted to comparative legal analysis of legal regulation of the institute of settlement agreement in Ukraine and Russia in the resolution of administrative disputes in court. The author draws attention to the differences and prospects of development of legislation in this area.